(untitled) (Research, Society and Development, 2022)
Local varieties of sweet corn from the far west of Santa Catarina, southern Brazil, show outstanding potential for several important agronomic traits aimed at sweet corn genetic breeding. However, there is no data in the literature on the general and specific combining ability of these varieties for the chemical quality of the grains and the interactions of the general and specific combining ability with the environment. The percentage of total soluble sugars, starch content, and the relationship between sugars and starch of the grains were evaluated in experiments designed in complete randomized blocks, with two replications, in two environments of this region. The splitting of the diallel analysis into general and specific combining ability indicated a predominance of non-additive effects for all evaluated traits and showed non-significant effects (p ≤ 0.05) of the interactions of the general and specific combining ability x environment. Varieties 2255A and 2276A presented a higher concentration of favorable alleles for increasing the chemical quality of grains. The intervarietal hybrids F1’s 2255A x 319A, 2255A x 2029A, 2255A x 2276A, Cubano x 2276A, 2276A x 2029A and 2255A x 741B stood out for interpopulation improvement. The biparental compounds derived from the combinations 2255A x 319A and 2255 x 2276A, the triple compound 2255A x 2276A x 2029A, and the quadruple compounds 2255A x 741B x 2276A x 319A and 2255A x 2276A x 2029A x 319A are the most suitable for the formation of composite populations followed by a cyclic process of recurrent selection, aiming to increase the chemical quality of the grains.